Relationship of football practice time and functional performance of lower limbs in children and adolescents - Cedin, Luísa (2018)
Introduction: football practice during childhood provides well-being along with several health benefits, including an improvement on functional performance. However, the long-term effects of sports practice on functionality are still uncertain on literature. Objective: the aim of the study was to verify the effects of football practice time on functional performance in children and adolescents. Materials and Methods: Forty football player boys for at least one year, aged 10 to 16, were evaluated. Functional performance was assessed by horizontal jump test and Single Hop Test. The correlation of practice time and functional performance was performed using the Pearson correlation coefficient. Results: the correlation between time of sports practice and horizontal jump was considered weak (r = 0.21), and the relationship of time of sports practice and lower limb dominant Single Hop Test (r = 0.23) and non-dominant (r = 0.13) was also weak. The relationship between time of sports practice and horizontal jump and Single Hop Test was considered weak. The comparison of Single Hop Test and horizontal jump between volunteers with different time practice showed no statistical significant difference (p > 0.05). Conclusion: the results suggest that football practice time above one year incites little effect on functional performance of lower limbs.